2023
DOI: 10.1186/s12888-022-04452-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of surf and hike therapy for U.S. active duty service members with major depressive disorder

Abstract: Background Major depressive disorder (MDD) is the most prevalent mental health disorder worldwide, including among U.S. service members. In addition to evidence-based treatments, activity-based approaches have been shown to effectively treat depressive symptoms, particularly when they occur in the natural environment. Methods This study compared two activity-based interventions, Surf Therapy and Hike Therapy, on depression outcomes among 96 active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 66 publications
3
11
1
Order By: Relevance
“…The Surf and Hike Therapy programs were conducted locally on a weekly basis for 6 consecutive weeks whereas the NVSSC was a week-long program in San Diego that typically required participants to travel. Unlike findings from the current study that showed a rebound in symptoms at the 3-month follow-up, results at 3 months following Surf and Hike Therapy demonstrated continued gains in depression outcomes for active duty service member participants ( Walter et al, 2023 ). While these findings cannot be directly compared, together they may suggest that programs with longer duration, more regular sessions, occur locally, or provide opportunities for continued engagement following the program period may facilitate sustained psychological improvements (e.g., Babyak et al, 2000 ; Mota-Pereira et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The Surf and Hike Therapy programs were conducted locally on a weekly basis for 6 consecutive weeks whereas the NVSSC was a week-long program in San Diego that typically required participants to travel. Unlike findings from the current study that showed a rebound in symptoms at the 3-month follow-up, results at 3 months following Surf and Hike Therapy demonstrated continued gains in depression outcomes for active duty service member participants ( Walter et al, 2023 ). While these findings cannot be directly compared, together they may suggest that programs with longer duration, more regular sessions, occur locally, or provide opportunities for continued engagement following the program period may facilitate sustained psychological improvements (e.g., Babyak et al, 2000 ; Mota-Pereira et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Across all psychological outcomes and both diagnostic groups, scores rebounded to preprogram levels at 3-month follow-up, suggesting that gains were not maintained. Walter et al (2023) used similar assessment methodology to this study to evaluate the duration of psychological effects following a randomized trial of surf and hike therapy. The Surf and Hike Therapy programs were conducted locally on a weekly basis for 6 consecutive weeks whereas the NVSSC was a week-long program in San Diego that typically required participants to travel.…”
Section: Discussionmentioning
confidence: 99%
“…Results were consistent with prior research reporting postprogram improvements in psychological and functional outcomes for outdoor exercise and recreation programs (Lundberg et al, 2011;Duvall and Kaplan, 2014;Rogers et al, 2014;Bennett et al, 2017;Crawford, 2017;Townsend et al, 2018;Walter et al, 2019Walter et al, , 2021Walter et al, , 2023. Though, in the current study, improvements in negative affect and social functioning were contingent on the number of sessions attended, with a greater number of sessions yielding stronger effects.…”
Section: Discussionsupporting
confidence: 90%
“…The NMCSD program offered an optional yoga practice for participants prior to the start of each Surf Therapy session (data were collected and analyzed). Further information on the Surf Therapy and Hike Therapy programs has been published elsewhere (see Walter et al, 2019Walter et al, , 2023. In early 2020, the NMCSD WII Wellness Program was forced to cancel all in-person group activities due to the COVID-19 pandemic.…”
Section: Programmentioning
confidence: 99%
See 1 more Smart Citation